Pengaruh Bermain Game Online terhadap Perkembangan Sosial Emosional Anak - Fithri Azni (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2017)
Technological developments brought many changes in the child's development. One form is the technological development of online games. The use of online games is more likely to give a negative influence on the development of a child's social-emotional. This is evident from research conducted on children who use the online game active in Kebun Sayur RT 05/RW 02, Bangko in hypothesis testing, the regression equation is Y = 48.553348 + 0,2092501X seen that the influence of online gaming (variable x ), the development of a child's social-emotional. (variable y) Kebun Sayur RT 05 / RW 02, Bangko calculated using simple linear regression got simply Fhitung> Ftabel or 5.0124> 4.196, then Ho is rejected. Thus a significant difference between playing online games against the development of a child's social-emotional. in Kebun Sayur RT 05/RW 02, Bangko. The online game that has made the child starts to lose time limits important in life, spend less time with family, and slowly pulled away from the normal routine of life of children. Child neglect social relationships with friends and ultimately his life become unmanageable because of the Internet, including online games.Keywords: Playing Online Games, Social-Emotional Development, Children